PROFIL KETERAMPILAN GEOMETRI SISWA TUNANETRA DI SEKOLAH INKLUSI PADA MATERI SEGIEMPAT ( Studi Kasus di SMP MIS Surakarta) - Ardiantoro, Gigih; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Universitas Sebelas Maret, 2017)
Abstract: This research is aimed to describe the skills in geometry of visually impaired inclusion students on rectangular learning. This research was qualitative research. The research subjects were grade IX student of SMP MIS Surakarta. There were 3 students consisting of 1 low vision student, 1 totally blind when he was 15 years old, and 1 totally blind since she was born. The procedure of selecting the subject used in this research was purposive sampling technique. The data of research was collected through interviews based on rectangular task. The data was analyzed based the theory skill in Geometry’s of Hoffer. The steps are : analyze all data are available from several sources, perform data reduction, compiling data in units, categorization the obtained data unit which shows each information on skill in Geometry of blind students in SMP MIS Surakarta as well as implementation of inclusion programs at SMP MIS Surakarta’s data. Skill in Geometry’s data was validated using time triangulation and implementation of inclusion programs at SMP MIS Surakarta’s data was validated using sources triangulation. The result of this research show that: 1) skills in geometry of low vision student cannot reach level 2 at all; 2) skills in geometry of student with totally blind when he was 15 year old can reach level 2 just on drawings skill. However, he cannot mastering level 0 on drawings skill well; 3) skills in geometry of student with totally blind since she was born cannot reach level 2 at all; 4) factors that affect skills in geometry of the students are availability of textbooks for students with visual impairment, the role of special guidances teachers, availability and uses of learning medium, teacher who has skills to handle student with visual impairment.Keywords: Geometry, Skills in Geometry, Visually impaired Student, Inclusions Student, Rectangular